Learner-centered teaching : five key changes to practice - Weimer, Maryellen, 1947- (San Francisco, CA : Jossey-Bass, A Wiley Imprint, 2013)
"In this new edition of the classic work, one of the nation's most highly regarded authorities on effective college teaching offers a comprehensive introduction to the topic of learner-centered teaching in the college and university classroom, including the most up-to-date examples of practice in action from a variety of disciplines, an entirely new chapter on the research support for learner-centered approaches, and a more in-depth discussion of how students' developmental issues impact the effectiveness of learner-centered teaching. Learner-Centered Teaching shows how to tie teaching and curriculum to the process and objectives of learning rather than to the content delivery alone"--
Includes bibliographical references and index.
LTIC
Book Finder Intentional
Keywords: College teaching; Learning, Psychology of; EDUCATION / Higher